Waste Disposal and Waste Management in Antarctica and the Southern Ocean - Bou Franch, Valentín (1996)
1. Introduction. 2. Waste generated in the Antarctic Treaty Area. A) The fragmentary approach. i) The Antarctic Treaty and the disposal of radioactive waste. ii) Waste generated by scientific activities. iii) Waste generated by tourist activities and non-governmental expeditions. iv) Waste generated by possible future mining activities. B) The comprehensive approach. i) The comprehensive legal framework. ii) General obligations. iii) Waste management planning and management practices. iv) Prohibited products, waste removal and waste disposal in the Antarctic Treaty Area. 3. Transboundary movements of hazardous waste and Antarctica. 4. Some conclusive remarks